Islamic Capital Market and Waqf - Hasan, Aznan; Rafidah, Neng; Hamber, Norliana; Mohd Zuhri, Muhammad Zhahiruddin; Khurshid, Usman (2013)
Various Studies have been conducted on the revival of waqf in modern times. Hence, there have been considerable researches conducted on the area of Islamic finance in various parts of the world to facilitate Waqf development towards improving the welfare of the Muslim ummah. It has also been said that waqf institutions provide a unique impetus for the growth of Islamic finance. The objective of this paper is to highlight how Islamic capital market instruments such as sukuk, real-estate investment trusts (REITs) and equity securities have facilitated the growth and development of institutions of waqf. However, there are several issues present for each of these instruments that need to be addressed before they can be utilized for this purpose. All in all, the collection of success stories presented in this paper is a testament of the thriving integration between waqf and contemporary Islamic finance.